Shaping Modern Vaccines: Adjuvant Systems Using MicroCrystalline Tyrosine (MCT®) - Heath, Matthew D.; Mohsen, Mona O.; de Kam, Pieter-Jan; Carreno Velazquez, Thalia L.; Hewings, Simon J.; Kramer, Matthias F.; Kündig, Thomas M.; Bachmann, Martin F.; Skinner, Murray A. (Frontiers in Immunology, 2020)
The concept of adjuvants or adjuvant systems used in vaccines exploit evolutionary relationships associated with how the immune system may initially respond to a foreign antigen or pathogen, thus mimicking natural exposure. This is particularly relevant during the non-specific innate stage of the immune response; as such, the quality of this response may dictate specific adaptive responses and conferred memory/protection to that specific antigen or pathogen. Therefore, adjuvants may optimise this response in the most appropriate way for a specific disease. The most commonly used traditional adjuvants are aluminium salts, however a biodegradable adjuvant, MCT®, was developed for application in the niche area of allergy immunotherapy (AIT), also in combination with a TLR-4 adjuvant – Monophosphoryl Lipid A (MPL®) – producing the first adjuvant system approach for AIT in the clinic. In the last decade, the use and effectiveness of MCT® across a variety of disease models in the preclinical setting highlight it as a promising platform for adjuvant systems, to help overcome the challenges of modern vaccines. A consequence of bringing together, for the first time, a unified view of MCT® mode-of-action from multiple experiments and adjuvant systems will help facilitate future rational design of vaccines while shaping their success.